2014
DOI: 10.1155/2014/651279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Tibial Components with Modular Stems Used in Primary TKA

Abstract: Due to the known potential for fretting and corrosion at modular junctions in orthopaedic implants, this retrospective study evaluated radiographic and clinical outcomes of 85 primary TKA patients implanted with modular stemmed tibial components and followed up for an average of 82 months. There was low incidence of tibial radiolucent lines, excellent functional outcomes, and no complications associated with stem modularity. The findings were comparable to the historical control study involving 107 TKA with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The L–S model caused high stress in host cancellous bone. High stress levels, particularly acting on weak cancellous bone, have been implicated as the predominant cause of tibial component loosening [ 23 , 24 ], and the abnormal stress pattern may cause stress shielding in long-term follow-up [ 25 , 26 ]. The stress pattern produced by load sharing between the implant and bone suggests that large soft bone grafting should be avoided in favor of grafting with hard bone to eliminate excessive stress in host cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…The L–S model caused high stress in host cancellous bone. High stress levels, particularly acting on weak cancellous bone, have been implicated as the predominant cause of tibial component loosening [ 23 , 24 ], and the abnormal stress pattern may cause stress shielding in long-term follow-up [ 25 , 26 ]. The stress pattern produced by load sharing between the implant and bone suggests that large soft bone grafting should be avoided in favor of grafting with hard bone to eliminate excessive stress in host cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…Fretting wear also occurs in other fields of technology, where a pair of elements touching each other is subjected to oscillatory tangential displacement. It follows from the review of literature that fretting wear is found in, for example, aviation industry [5][6][7], in medicine [8][9][10] in orthopaedic items connecting fractured limbs and in artificial joints, as well as in the automotive industry [11].…”
Section: Fretting Wearmentioning
confidence: 99%
“…in the modular designs of some TKA components [8] . This additional junction, which was not present in the original monobloc model, is a potential source of metal debris [1,6,9,10] .…”
Section: International Journal Of Orthopaedicsmentioning
confidence: 99%
“…Metal debris generated at this junction is thought to be due to fretting corrosion at the metal on metal interface [10] . Corrosion and subsequent micro motion at the trunnion deposits metal debris within local soft tissues [2,8] . This process has been shown to cause an adverse reaction to metal debris (ARMD) and is associated with increased prosthetic failures [9,11 -13] .…”
Section: International Journal Of Orthopaedicsmentioning
confidence: 99%